Hepatic alveolar echinococcosis infection induces a decrease in NK cell function through high expression of NKG2A in patients - Abulizi, Abuduaini; Tuergan, Talaiti; Shalayiadang, Paizula; Zhang, Chuanshan; Zhang, Ruiqing; Jiang, Tiemin; Guo, Qiang; Wang, Hui; Li, Liang; Lin, Renyong; Shao, Yingmei; Aji, Tuerganaili (Frontiers in Immunology, 2025)
Echinococcus multilocularis larval tapeworm infection in humans is considered a serious public health issue. The immune interaction between parasites and their hosts is extremely important. NK cells are known innate immune cells that play important roles during infection and tumour progression. However, the possible role of NK cells in hepatic alveolar echinococcosis is not completely clear. In this study, we investigated the functional decrease in NK cells in hepatic alveolar echinococcosis (AE) patients.MethodsUsing human liver tissue samples from 10 patients with hepatic AE, flow cytometry was used to detect the expression of NKG2A molecules on the surface of NK cells, and the correlations between NKG2A+ expression and lesion size, alkaline phosphatase (ALP) levels in close lesion tissues (CLTs) and distal lesion tissues (DLTs) in the liver, and the secretion of functional molecules by NKG2A+ NK cells were analysed.ResultsThe expression of NKG2A on CD56dim and CD56bright NK cells in DLTs and CLTs revealed that the percentage of NKG2A+CD56dim NK cells in CLTs was significantly greater than that in DLTs. There was a negative correlation between the expression of NKG2A on NK cells in the CLT and alkaline phosphatase. Additionally, we analysed IFN-γ, TNF-α, granzyme B, and perforin production in NK cells. There was a significant reduction in IFN-γ production in CLTs compared with DLTs. There is a negative correlation between IFN-γ production levels and NKG2A expression in NK cells from the CLT. The capacity of NKG2A+ NK cells from CLT regions to produce IFN-γ and granzyme B was also significantly decreased. In contrast, the perforin level produced by NKG2A+ NK cells was much greater than that produced by NKG2A− NK cells. We also analysed the correlation between the ratio of the NKG2A expression area in CLT and DLT tissues and the PET–CT value and found a positive correlation between NKG2A expression and the PET–CT value.ConclusionThe increased expression of NKG2A in NK cells induced a reduction in IFN-γ production, and the increased expression of NKG2A may improve lesion activity and fibrosis, which may be helpful for treating hepatic alveolar echinococcosis via immunity.